Freeze-Drying Microencapsulation of Ruellia tuberosa L. Extracts: A Comparative Study Using Different Polymers as Encapsulants - Gunawan, Firza Rajasa; Ulfa, Siti Mariyah; Safitri, Anna (Indonesian Journal of Chemistry, 2025)
Ruellia tuberosa L. leaf and root extracts have been investigated for their biological activity and potential health advantages, including their antidiabetic, antioxidant, and antidiuretic qualities. This research evaluates the freeze-drying microencapsulation of R. tuberosa L. extracts using gum Arabic, maltodextrin, and their combination as coating materials. The resulting microcapsules were tested for encapsulation efficiency, biological activity, and controlled release. Characterization techniques included scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and particle size analysis (PSA). The choice of encapsulant significantly influenced encapsulation efficiency, morphology, and biological activity. Microcapsules using a combination of gum Arabic and maltodextrin exhibited more spherical shapes and smaller particle sizes than those using either material alone. Alpha-amylase inhibition tests showed that microcapsules effectively inhibit the enzyme, with the coating combination performing best, followed by gum Arabic and then maltodextrin. All microcapsules exhibit moderate antioxidant activity, again in the same order. The active compound release was greater at pH 7.4 compared to pH 2.2 from 0 to 120 min. Therefore, freeze-drying microencapsulation with biodegradable polymers is a viable method for delivering the health benefits of R. tuberosa L. extracts, yielding a convenient powder form suitable for drug delivery systems.